“MANGGARAI TRANSIT HUB” TERINTEGRASI DENGAN HUNIAN VERTIKAL - Lucky Brian Hartono; Suwandi Supatra (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The city of Jakarta is now a center for mobility activities with various fields carried out by the community every day. However, the vastness of the city of Jakarta causes a lack of effective control and planning of space and functions in each area. Because of this, there is regional degradation and negative spaces such as slums and illegal settlements and abandoned buildings arise. In addition, less affordable modes of transportation between important places are present around the area. Therefore, it is necessary to have a building with the function of a housing program and public transportation transit space that is affordable by urban communities. The Manggarai area is a major transit center point that has existed since the Dutch colonial period and has a function as a large center for public transportation such as trains and city buses. However, it can be seen from the existing area, that there is no increase in regional development and the emergence of many negative and inefficient spaces in the use of space in the Manggarai area. One of issues is the slum settlement that have been built on the riverbanks and side of   railway line, causing insufficient indoor and outdoor space in the Manggarai area. The design method is "Contextual" which is applied with a contextual approach that occurs in the Manggarai area. In conclusion, the project will be a mixed-used building in which there is a vertical residential activity program and presents a transit space for transportation modes by applying a spatial atmosphere that characterizes the locality of the Manggarai area. The design of the Transit Hub is designed with the implication of aspects of area characterization and saving energy and being able to facilitate the community in activities. Keyword : housing; settlement; transit Abstrak Kota Jakarta kini menjadi pusat mobilitas kegiatan dengan berbagai bidang yang dilakukan oleh masyarakat setiap harinya. Namun, luasnya kota Jakarta menyebabkan kurangnya pengontrolan dan perencanaan ruang dan fungsi di setiap kawasan secara efektif. Karena itu, terjadi adanya degradasi kawasan dan timbul ruang-ruang negatif seperti permukiman kumuh dan ilegal serta bangunan yang terbengkalai. Selain itu, Moda transportasi yang kurang terjangkau antar tempat penting yang hadir di sekitar kawasan. Maka itu, dibutuhkan hadirnya sebuah bangunan dengan fungsi program hunian dan ruang transit transportasi umum yang terjangkau oleh masyarakat perkotaan. Kawasan Manggarai merupakan satu titik pusat transit besar yang sudah ada sejak masa kolonial belanda dan memiliki fungsi sebagai pusat besar moda transportasi umum seperti Kereta api dan Bus kota. Namun, terlihat melalui eksisting kawasan, pengembangan kawasan tidak ada peningkatan dan timbulnya banyak ruang-ruang negatif dan tidak efisien dalam pemanfaatan ruang pada kawasan Manggarai. Salah satu isu utama yaitu permukiman kumuh yang terbangun di bantaran sungai dan sisi jalur kereta api menyebabkan kurang memadainya ruang luar maupun dalam Kawasan Manggarai. Metode perancangan yang digunakan adalah “kontekstual” yang diterapkan dengan pendekatan kontekstual yang terjadi pada Kawasan Manggarai. Sebagai kesimpulan , proyek akan berupa sebuah mixed-used building yang didalamnya terdapat program aktivitas hunian secara vertikal dan menghadirkan ruang transit moda transportasi dengan menerapkan adanya suasana ruang mengkarakterisasi lokalitas dari kawasan Manggarai. Perancangan Transit Hub dirancang dengan adanya mengimplikasikan aspek karakterisasi Kawasan dan hemat energi serta mampu memudahkan masyarakat dalam aktivitas.